The Consequence of the Presence of Ribonucleotide for ds-DNA’s Electronic Properties: Preliminary Theoretical Studies - Boleslaw T. Karwowski (Cells, 2025)
The genome is continuously exposed to different harmful factors whose activity causes different types of lesions. On the other hand, during the DNA replication process, a ribonucleoside (rN) can be inserted more frequently than the occurrence of DNA damage in the genome. Notably, it can be expected that their presence and chemical lability change the electronic properties of the double helix. In this study, a short ds-oligo with a single rN was taken into consideration. The ground-state molecular geometry was obtained at the M06-2x/D95* level of theory in the aqueous phase, while the energy and vertical and adiabatic electron affinity and ionisation potential were obtained at M06-2x/6-31++G**. The obtained results indicate that the 3′,5′-phosphodiester bond cleavage is favourable after the adiabatic cation and anion states are achieved by ds-DNA. Moreover, the lowest ionisation potential and highest electron affinity of 2.76 and 5.55 eV, respectively, which make it a suitable endpoint for electrons and holes, have been found for the final product that contains a single-strand break. Additionally, after the internucleotide 3′,5′→2′,5′ bond migration process, proton-coupled electron transfer was found to occur. In this article, the electronic properties of short ds-DNA fragments with ribonucleoside inserts are reported for the first time. The obtained results suggest that rNs can play a significant role in the communication of repair and replication proteins via electron transfer, especially after rearrangement. Moreover, the discussed internucleotide bond stability changes after one-electron oxidation or reduction and can support new radiotherapy strategies that are safer and more effective. Further theoretical and experimental studies are highly warranted.